PERANCANGAN SISTEM KEMUDI GOKAR LISTRIK - Judisthira Frelly Mamahit; Stenly Tangkuman; Michael Rembet (JURNAL POROS TEKNIK MESIN UNSRAT, 2016)
The function of steering system is to change the directions of wheel. The purpose  of this design is to be obtained a simple steering system. Beside that, in this work have been determined stresses, they are shear stress due to torsion and normal stress due to axial load and bending. Therefore, the strength of mechanism can be obtained. Based on the calculation, maximum  shear stress induce in steering system is 4,11 Pa and maximum normal stress is 0,206 Pa. moreover this design have been  obtained steering angle for some values of angle. The final  result of this design is some technical drawing that presented detail dimension of components. Keywords : Design, Steering System, Stress